Antibiotic uptake through porins located in the outer membrane of Gram-negative bacteria. (3rd April 2021) - Winterhalter, Mathias
ABSTRACT: Introduction : Making selective inhibitors of novel Gram-negative targets is not a substantial challenge – getting them into Gram-negative bacteria to reach their lethal target is the bottleneck. Poor permeability of the antibiotic requires high concentration causing off target activity. The lack of simple experimental techniques to measure antibiotic uptake as well as the local concentration at the target site creates a particular bottleneck in understanding and in improving the antibiotic activity. Areas covered : Here we recall current approaches to quantify the uptake. For a few antibiotics with known evidence for channel-limited permeation, the flux across a single OmpF or OmpC channel has been measured. For a typical concentration gradient of 1 µM of antibiotics the uptake varies between one up to few hundred molecules per second and per channel. Expert opinion : The current research effort is on quantifying the flux for a larger list of compounds on a cellular (mass spectra, fluorescence) or at single channel level (electrophysiology). A larger dataset of single channel permeabilities under various condition will be a powerful tool for understanding and improving the activity of antibiotics.